Protistan-Bacterial Microbiota Exhibit Stronger Species Sorting and Greater Network Connectivity Offshore than Nearshore across a Coast-to-Basin Continuum - Ping Sun (American Society for Microbiology, 2021)
Microbial organisms play a crucial role in global nutrient cycling. Few studies have attempted to simultaneously investigate the community assembly of microeukaryotes and prokaryotes and their association patterns in oceanic waters.